Effect of dose and field strength on enhancement with paramagnetic contrast media. - Lindsey, R O; Yetkin, F Z; Prost, R; Haughton, V M (American Journal of Neuroradiology, 1994)
PURPOSE To compare contrast enhancement per unit of dose of contrast medium in MR imaging at 0.5 and 1.5 T. METHODS Contrast enhancement in images made at 0.5 and 1.5 T after 0.1 mmol/kg of gadopentetate dimeglumine and 0.3 mmol/kg of gadodiamide was measured and the degree of contrast enhancement in the cavernous sinus and pituitary gland compared. RESULTS At both field strengths and both contrast medium doses, contrast enhancement was noted in the cavernous sinus, pituitary gland, infundibulum, maxillary sinus mucosa, falx cerebri, and choroid plexus on inspection of images. Enhancement was significantly and conspicuously less in the cavernous sinus and pituitary gland at 0.5 T (96% and 33%, respectively) than at 1.5 T (160% and 102%, respectively). No tissues were identified that enhanced only with the larger dose or higher field strength. CONCLUSION In tissues that normally enhance after intravenous administration of gadolinium chelates, enhancement is greater at 1.5 T than at 0.5 T.